Design and Implementation of Sterilization Chamber with Ozone and UV-C Light to Break the Transmission of Covid-19 - Muhammad Latifur Rochman; Lilik Budiyarto; Muhammad Iqbal Al-Fikri; Khoirul Fa’i; Prasasti Bayu Aji Pramono; Riyan Tri Aditya Pamungkas; Baginda Pangidoan Tanjung; Refaldy Pristiwantoro; Widha Bagus Fahriansyah; Agung Setyo Pambudi; Ahmad Irfan; Riyan Adhy Pratama; Lalank Samudra Mukti Hidayat; Setyo Widiantoro; Darmawan Rois; Muhammad Mauludin Kharim; Wahyu Danu Romadlon; Dwi Restianto; Muji Setiyo; Budi Waluyo; Bagiyo Condro Purnomo; Suroto Munahar; Noto Widodo; Saifudin Saifudin (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The emergence of Corona Virus Disease 19 (Covid-19) required a new method to control its spread. During this time, controlling COVID-19 was carried out by implementation of a sterilization chamber using a liquid-based disinfectant. However, the use of liquid-based disinfectants has been evaluated to be less effective because it allows disrupting the respiratory tract. Therefore, this work presents a negative pressure sterilization chamber using Ozone and UV-C lamp. Ozone has been recommended by the Indonesian Institute of Sciences (LIPI) as a substitute for liquid-based disinfectants. In addition, to maximize performance, the chambers are added with UV-C lamps. The negative pressure sterilization chamber with Ozone and ultraviolet lamps was successfully created with the main parts of the cubicle chamber, an Ozone generator, at least one ultraviolet lamp, exhaust fan, switch, and a timer. The negative pressure sterilization chamber with Ozone and ultraviolet lamps according to this work, where the Ozone supply from the Ozone generator is made automatically to the door opening and closing. The duration of the Ozone supply was regulated by a timer. Then, the ultraviolet lamp can be activated together with Ozone or independently. With the implementation of this sterilization chamber, the spread of the Covid-19 virus is expected to be suppressed in a safer way than using liquid-based disinfectants.